Innovative Strategies of Training Mechanism of Higher Education for New Entrepreneurial Talents - Wei, Fengyun (Frontiers in Psychology, 2021)
With the development of the social economy, more and more talents are required in economic construction and innovation. The study aims to cultivate new entrepreneurial talents and promote the overall development of new ventures. First, the entrepreneurial ability of new entrepreneurial talents is analyzed, and the feasibility of improving the entrepreneurial ability of new entrepreneurial talents is verified. Second, the architecture is designed for improving the entrepreneurial ability of new entrepreneurial talents. About 350 employees in 20 ventures in Xi'an, Shaanxi Province are randomly selected as the subjects for a questionnaire survey (QS). Three-fifty questionnaires are distributed and 300 are collected. Descriptive statistics are used to analyze the 300 valid questionnaires. Then, the relationship between the psychological states of new entrepreneurial talents and their entrepreneurial ability is explored, and the influencing factors in the development of new entrepreneurial talents are analyzed. The results show that the number of employees in most ventures is between 250 and 400 and the age of the employees in the tested new ventures is between 35 and 40. More than one-third of employees are managers and over 86% of them have a degree of bachelor or above. The scores of the scale of the psychological state of new entrepreneurs are high. This shows that most of the new entrepreneurs have a high educational level, strong motivation for entrepreneurial success, and great self-confidence, which are essential in the process of innovative training. Therefore, the talent training of new entrepreneurial talents should be based on a high educational level and focused on practice.